Pengaruh Kepemimpinan Distributif dan Kewirausahaan Kepala Sekolah terhadap Pencapaian SNP di SMK Negeri 1 Pajangan - Margi Wisma Gandi; Darmono Darmono; Muhammad Nuruzzaman; Indah Wahyuni (Jurnal Pendidikan Teknik Sipil, 2022)
ABSTRACTThis study aims to determine (1) the level of attainment of the National Education Standards, (2) the level of the principal's distributif leadership, (3) the level of entrepreneurial leadership of school principals, (4) the influence of the principal's distributif leadership on the achievement of the National Education Standards, (5) the influence of leadership. entrepreneurship of school principals on the achievement of National Education Standards, (6) the influence of distributif leadership and entrepreneurship of school principals together on the achievement of National Education Standards, and (7) the relationship of distributif leadership to the entrepreneurial leadership of school principals. This research is a quantitative research. The object of research in this study is SMK Negeri 1 Pajangan. The data collection technique used a questionnaire.  Instrument  validation  uses  product  moment  correlation  and  reliability  uses  the  Alpha Croncbach formula. The data analysis technique used descriptive analysis and multiple regression. The results showed that: (1) the level of achievement of the National Education Standards obtained an average score of 85.98% in the very suitable category, (2) the level of distributif leadership obtained an average achievement of 83.55% in the very suitable category, (3) ) the level of entrepreneurial leadership attainment of the principal is 74.2% (4) there is a significant positive effect of distributif leadership on the National Education Standards, as evidenced by the tcount of 2.503> t table 2.048 at the 5% significance level and the correlation coefficient of 0.545, (5) There is a positive influence between the entrepreneurial leadership of the principal on the achievement of the National Education Standards, as evidenced by the tcount of 0.514> 0.355 at a significance level of 5% and a correlation of 0.514, (6) there is a positive influence between distributif leadership and entrepreneurship of school principals together. against the achievement of the National Education Standards, it is evident an with Fcount of 9.269> Ftable 3.348 at a significance level of 5% and a correlation value of 0.631 with an effective contribution of 29.8%. and (7) there is a relationship between the principal's distributif leadership and the principal's entrepreneurial leadership, as evidenced by the correlation coefficient 0.410> 0.355, p = 0.05.Keywords: Leadership, Distributif, Entrepreneurship, Principal, SNPABSTRAKPenelitian ini bertujuan untuk mengetahui (1) tingkat pencapaian Standar Nasional Pendidikan, (2) tingkat kepemimpinan distributif kepala sekolah, (3) tingkat kepemimpinan kewirausahaan kepala sekolah (4) pengaruh kepemimpinan distributif kepala sekolah terhadap pencapaian Standar Nasional Pendidikan, (5) pengaruh kepemimpinan kewirausahaan kepala sekolah terhadap pencapaian Standar Nasional Pendidikan, (6) pengaruh kepemimpinan distributif dan kewirausahaan kepala sekolah secara bersama-sama terhadap pencapaian Standar Nasional Pendidikan, dan (7) hubungan kepemimpinan distributif terhadap kepemimpinan kewirausahaan kepala sekolah. Penelitian ini merupakan penelitian kuantitatif. Objek penelitian dalam penelitian ini adalah SMK Negeri 1 Pajangan. Teknik pengumpulan data menggunakan angket. Validasi instrument menggunakan product moment correlation dan reliabilitas menggunakan rumus Alpha Croncbach. Teknik analisis data menggunakan analisis deskriptif dan regresi berganda. Hasil penelitian menunjukan bahwa: (1) tingkat pencapaian Standar Nasional Pendidikan memperoleh skor rata-rata 85,98% dengan kategori sangat sesuai, (2) tingkat kepemimpinan distributif memperoleh pencapaian rata-rata sebesar 83,55% dengan kategori sangat sesuai, (3) tingkat pencapaian kepemimpinan kewirausahaan kepala sekolah pencapaian sebesar 74,2% (4) terdapat pengaruh positif yang signifikan kepemimpinan distributif terhadap Standar Nasional Pendidikan, dibuktikan dengan thitung sebesar 2,503 > ttabel 2,048 pada taraf signifikansi 5% dan koefisien korelasi sebesar 0,545, (5) terdapat pengaruh positif antara kepemimpinan kewirausahaan kepala sekolah terhadap pencapaian Standar Nasional Pendidikan, dibuktikan dengan nilai thitung sebesar 0,514 > ttabel 0,355 pada taraf signifikansi 5% dan korelasi sebesar 0,514, (6) terdapat pengaruh positif antara kepemimpinan distributif dan kewirausahaan kepala sekolah secara bersama-sama terhadap pencapaian Standar Nasional Pendidikan, dibuktikan dengan Fhitung sebesar 9,269 > Ftabel 3,348 pada taraf signifikansi 5% dan nilai korelasi sebesar 0,631 dengan sumbangan efektif sebesar 29,8%. dan (7) terdapat hubungan antara kepemimpinan distributif kepala sekolah terhadap kepemimpinan kewirausahaan kepala sekolah, dibuktikan dengan koefisien korelasi 0,410 > 0,355, p = 0,05.